Physiological characteristics during the formation of aromatic components in xylem of Aquilaria sinensis induced by exogenous substances - Pang, Shengjiang; Li, Zhongguo; Zhang, Qingqing; Tian, Zuwei; Deng, Shuokun; Zhang, Pei; Liu, Shiling; Yang, Baoguo; Zhou, Zaizhi (Frontiers in Plant Science, 2024)
An inductive combination of plant growth regulators, inorganic salts, and fungi is essential for the formation of aromatic components in the xylem of Aquilaria sinensis. However, the dynamics of xylem physiology and the relationships between physiological properties and aromatic components after artificial induction remain unclear. In this study, the changes in physiological properties of A. sinensis xylem during induction were determined and analyzed under four induction treatments and a control group. The defense hormone contents of jasmonic acid, salicylic acid, aminocyclopropane-1-carboxylic acid, and abscisic acid obtained from the four induction treatments increased significantly.However, the concentrations of gibberellin and indoleacetic acid were decreased compared to the control group. An initially upward and then downward trend was observed in the main antioxidant enzyme activities. Additionally, malonaldehyde content decreased obviously, while proline content tended to increase and then decrease as induction continued. The total and soluble sugar content was evidently reduced after treatment, and the soluble sugar content recovered more rapidly with time. Thirty-three aromatic components were identified in all treatments, and the primary aromatic components were terpenes, aromatics and chromones, the relative contents of which varied among treatments. These results provide new insights for optimization and innovation of agarwood induction techniques by exploring the formation of aromatics in the xylem of A. sinensis and its physiological responses following induction with exogenous substances (ethephon, NaCl, CaCl2 and fungal mixed solution).